The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/13550281003682513
|View full text |Cite
|
Sign up to set email alerts
|

Does highly active antiretroviral therapy improve neurocognitive function? A systematic review

Abstract: Highly active antiretroviral therapy (HAART) reduces the incidence of human immunodeficiency virus (HIV) dementia (HAD), whereas the overall prevalence appears to have increased. Recent changes to diagnostic nosology have emphasized the presence of neurocognitive deficits. Uniform methods of ascertaining neuropsychological impairment and excluding confounding causes are critical to between-study comparison. We conducted a systematic review on all studies that use single-cohort prospective treatment effect desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 49 publications
3
88
0
Order By: Relevance
“…However, 1 year is not an unreasonable follow-up period, given that it has been shown that significant cognitive improvement is usually seen within 6 months of starting ART. [11] It could be argued that a selection bias exists in this study, in terms of excluding those participants not on suppressive ART regimens for ≥10 months. These participants may have had poorer cognitive function and therefore greater difficulty in accessing and adhering to ART.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 1 year is not an unreasonable follow-up period, given that it has been shown that significant cognitive improvement is usually seen within 6 months of starting ART. [11] It could be argued that a selection bias exists in this study, in terms of excluding those participants not on suppressive ART regimens for ≥10 months. These participants may have had poorer cognitive function and therefore greater difficulty in accessing and adhering to ART.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[8][9][10] ART typically produces a significant improvement in neurocognitive status within 6 months of treatment. [11] This does not, however, imply a complete recovery in all cases. In fact, incident cases of cognitive dysfunction can still arise while patients are on suppressive ART regimens.…”
mentioning
confidence: 99%
“…One systematic review reported that HAART can improve cognition among HIV-infected individuals [89], but a subsequent review suggested that antiretroviral therapy did not improve memory functioning and may even have a negative impact [90]. Thus, it will be important to clarify the impact that these medications have on neurocognitive functioning in order to tease out the unique contributions of marijuana use.…”
Section: Critique Of the Current Literature And Future Research Priormentioning
confidence: 99%
“…10,13-14 As yet there are no treatment guidelines for HAD, but it is generally accepted HAART improves cognition. 15 Whilst we await recommendations on specific ARV regimes or other treatments, we should initiate patients with HAD on ARVs. Given the burden of HAND and direct benefits of starting ARVs, there is an urgency to develop rapid screening tools to detect and monitor HAND.…”
Section: Hiv-associated Dementia (Had)mentioning
confidence: 99%